Pengaruh Growth Opportunities, Intensitas Modal, dan Debt Covenant Terhadap Konservatisme Akuntansi: Kajian Literatur Review - Daffa Putra Ananto; Mochammad Baehaqi; Dien Noviany Rahmatika (Akuntansi, 2024)
Accounting conservatism is a principle that tends to recognize very rapid losses that usually will cause a delay in recognized income so that it can be realized. This principle is important to ensure more prudent and reliable financial statements. However, any causes that have an impact on the conservative financial reporting process are still debated among researchers and practitioners. This study aims to investigate and show how Growth Opportunities, Capital Intensity, and Debt Covenants affect Accounting Conservatism. This study uses an approach in the form of a Structured Literature Review (SLR), where several journals that have been published between 2016 and 2023 will be analyzed systematically. A total of 59 journals are used as sources in this study. The literature will be grouped according to relevant concepts and arranged into themes that are used to further explore the effects that accounting conservatism will have. The end of the study shows that Growth Opportunities have absolutely no impact on Accounting Conservatism, which shows that companies with high growth opportunities tend to be less conservative in their financial reporting. On the other hand, Capital Intensity shows a significant positive effect, which means that companies with high Capital Intensity are more likely to implement Accounting Conservatism. Meanwhile, Debt Covenant does not show a significant effect on accounting conservatism.